Showcasing African Story through Multimedia Performance: A Review of Rejected Blessing - Lilian Okoro; Uwaoma C. Nwazue (Pascasarjana Universitas Negeri Makassar, 2022)
Oral story telling as an African tradition used in safeguarding and transferring values from one generation to another has come under serious threat as a result of the modernization and digitalization of the arts. These oral traditions, like folk stories, are sometimes told and performed under the moonlight games, but seem to be going extinct with the advent of digital platforms where children can watch only foreign content, thereby forgetting African didactic content which inculcates values in them. Using the performance of Rejected Blessing in a multimedia approach, this study sees the infusion of media elements as a catalyst in reinvigorating and sustaining African storytelling and also refreshing the interest of the theatre audience in watching live performances. The methodology of exploring the multimedia and the stage in presenting the play is the recommendation of this paper. This paper also recommends that the infusion of multimedia creates a new spice for children and theatre-goers who may have lost interest in African traditional stories due to the influence of new media. Finally, this study suggests more experimentation with multimedia in order to sustain the values of African storytelling.